A cluster of melioidosis infections in hatchling saltwater crocodiles (Crocodylus porosus) resolved using genome-wide comparison of a common north Australian strain of Burkholderia pseudomallei. Issue 8 (21st August 2019) - Rachlin, Audrey; Kleinecke, Mariana; Kaestli, Mirjam; Mayo, Mark; Webb, Jessica R.; Rigas, Vanessa; Shilton, Cathy; Benedict, Suresh; Dyrting, Kitman; Currie, Bart J.
Abstract : Burkholderia pseudomallei is a Gram-negative saprophytic bacillus and the aetiological agent of melioidosis, a disease of public-health importance throughout Southeast Asia and northern Australia. Infection can occur in humans and a wide array of animal species, though zoonotic transmission and case clusters are rare. Despite its highly plastic genome and extensive strain diversity, fine-scale investigations into the population structure of B. pseudomallei indicate there is limited geographical dispersal amongst sequence types (STs). In the 'Top End' of northern Australia, five STs comprise 90 % of the overall abundance, the most prevalent and widespread of which is ST-109. In May 2016, ST-109 was implicated in two fatal cases of melioidosis in juvenile saltwater crocodiles at a wildlife park near Darwin, Australia. To determine the probable source of infection, we sampled the crocodile enclosures and analysed the phylogenetic relatedness of crocodile and culture-positive ST-109 environmental park isolates against an additional 135 ST-109 B. pseudomallei isolates from the Top End. Collectively, our whole-genome sequencing (WGS) and pathology findings confirmed B. pseudomallei detected in the hatchling incubator as the likely source of infection, with zero SNPs identified between clinical and environmental isolates. Our results also demonstrate little variation across the ST-109 genome, with SNPs in recombinogenic regions and one suspected case of ST homoplasy accounting for nearly all observed diversity. Collectively, this study supports the use of WGS for outbreak source attribution in highly recombinogenic pathogens, and confirms the epidemiological and phylogenetic insights that can be gained from high-resolution sequencing platforms.